2014
DOI: 10.1109/mprv.2014.77
|View full text |Cite
|
Sign up to set email alerts
|

Text Input on a Smart Watch

Abstract: T ext entry is a key component of many smartphone applications. The recent release of smart watches has met considerable interest, but without text entry, interaction is frustratingly limited-users can see posts, short messages, and emails but can't reply using the watch. As part of our ongoing work, we outline a text entry approach for smart watches, describe our initial prototype, and discuss the outcomes of our lab-based evaluation of the prototype. Text Entry on Small DevicesBefore the widespread adoption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Zoomboard [16]) or larger ambiguous keys (e.g. [11]). An interesting challenge is whether a hybrid system could allow seamlessly switching between sentence-based decoding and other approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Zoomboard [16]) or larger ambiguous keys (e.g. [11]). An interesting challenge is whether a hybrid system could allow seamlessly switching between sentence-based decoding and other approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Their user study with 16 participants, and with Zoomboard as a baseline technique, revealed that the prototype supports novice to expert behaviors and improves a users' performance to achieving a high entry speed (19.58 words per minute (WPM), 15% faster than the existing baseline technique) (Chen et al, 2014). Similarly, Komninos & Dunlop (2014) prototype is similar to a QWERTY keyboard and divides the keyboard into six large keys (Oney et al, 2013;Chen et al, 2014;Komninos & Dunlop, 2014) Other researchers explored how smartwatches can assist in gaining awareness of team members, coordinating their activities, and displaying contextual information. However, they did not perform a usability study with users to test their prototype.…”
Section: Smartwatch Designmentioning
confidence: 99%
“…Instead of the physical button recent studies have developed text input methods based on touchscreen interface Komninos and Dunlop, 2014;Cho et al, 2014). Oney et al (2013) proposed ZoomBoard based on a qwerty keyboard layout Table 1 Summary of major related researches.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is time consuming because the system requires zoom in/out repeatedly to select letters. Komninos and Dunlop (2014) proposed a 6 key layout which group 3 to 5 letters from the alphabets (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation